(untitled) (Al-Academy, 2023)
The researcher was interested in studying a crucial aspect of the systematic world music culture. He highlights the analysis of the harmonic construction in the musical compositions of the artist Khalil Ismail, where harmony is a significant Western musical science, a pillar of the structure of instrumental and vocal music.It depends on the compositions of vertical sounds performed simultaneously, as tones coincide and are sometimes dissonant to give sound resonance that enriches musical work and attracts recipients. Hence, the researcher has many questions, including: Can the composition of the writings of the artist Khalil Ismail determine in an objective research framework? Is there a study on this subject in some detail? which leads the researcher to search for answers.However, no previous studies have had found in this regard; The researcher is therefore convinced that there is an urgent need to write this research and study the all-important part of his harmony construction.